Jadassohn-Lewandowsky syndrome. Report of the first pediatric case in Cuba - Migdalis Hidalgo Muñiz; Aracelis Hernández García; Andrés Andrés Matos; Yadelis Maldonado Martínez (Medisur)
Jadassohn-Lewandowsky syndrome or congenital pachyonychia type 1 belongs to the rare diseases’ group. Worldwide, less than a thousand cases have been described to date and the one that is now published constitutes the first pediatric age report in Cuba. A seven-years-old male patient admitted to the Pediatric Clinic Service at the Holguín Provincial Pediatric Hospital with a history of yellow and hypertrophic nails since he was nine months old. The physical examination confirmed the presence of hypertrophic nail dystrophy in all 20 nails, keratosis follicularis on the elbows, hands and lower limbs, focal plantar keratoderma and oral leukokeratosis. An autosomal dominant inheritance pattern was identified. Based on the phenotypic characteristics and family history, the case presented was classified as congenital pachyonychia type 1, for which there is still no cure and gene therapy is under investigation. Due to the rareness of the disease and being the first pediatric age case in Cuba, its publication was decided.